MULTIKULTURALISME SEBAGAI WACANA KRITIKAL: ANTARA REALITAS SOSIAL DAN IDEAL FILOSOFIS - Diaz, Tirta Alim Wiliam; Nofriana, Ita; Qipti, Ersa Melindi; Aprini, Kharisma (Bahasa Indonesia, 2025)
Multiculturalism is a philosophical and social concept that emphasizes the recognition of cultural diversity, advocating for principles of justice, equality, and respect for differing cultural identities. While the ideal of multiculturalism is widely accepted in theory, its application in social practice often faces significant challenges, such as social inequality, discrimination, and inter-cultural tensions. This study examines the relationship between the philosophical ideal of multiculturalism and the social realities faced by contemporary multicultural societies. It argues that the gap between theoretical frameworks and real-world practices can be bridged through critical dialogue, a commitment to inclusive policies, multicultural education, and the active role of media in fostering inter-cultural understanding. The research also underscores the importance of collective awareness within society regarding diversity as a vital social resource for promoting social cohesion and justice. By analyzing these dimensions, the study demonstrates how multiculturalism, when effectively implemented, can transcend its theoretical aspirations and become a transformative force in creating just and harmonious societies. Overall, this research aims to provide insights into how societies can bridge cultural differences, not only through policies but by fostering mutual respect and shared values in everyday life.